2019
DOI: 10.1021/acs.jpcb.9b09106
|View full text |Cite
|
Sign up to set email alerts
|

Modeling DNA Flexibility: Comparison of Force Fields from Atomistic to Multiscale Levels

Abstract: Accurate parametrization of force fields (FFs) is of ultimate importance for computer simulations to be reliable and to possess a predictive power. In this work, we analyzed, in multi-microsecond simulations of a 40-base-pair DNA fragment, the performance of four force fields, namely, the two recent major updates of CHARMM and two from the AMBER family. We focused on a description of double-helix DNA flexibility and dynamics both at atomistic and at mesoscale level in coarse-grained (CG) simulations. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 70 publications
4
60
0
Order By: Relevance
“…DNA can be described by several force fields such as parmbsc1 ( 38 ), parmOL15 ( 39 ), CHARMM27 ( 40 , 41 ), and CHARMM36 ( 42 ). Since recent benchmarks showed similar performance of parmbsc1 and parmOL15 ( 43–45 ) and overall better reliability than CHARMM force fields ( 44 , 46 , 47 ), we employed parmbsc1 in this work. Each DNA was immersed into a truncated octahedral box filled by the TIP3P water, ( 48 ) and 24 (class I ) or 28 (classes II, III, C1, C2, H1, H2, H3 ) sodium ( 49 ) cations to maintain electroneutrality.…”
Section: Methodsmentioning
confidence: 99%
“…DNA can be described by several force fields such as parmbsc1 ( 38 ), parmOL15 ( 39 ), CHARMM27 ( 40 , 41 ), and CHARMM36 ( 42 ). Since recent benchmarks showed similar performance of parmbsc1 and parmOL15 ( 43–45 ) and overall better reliability than CHARMM force fields ( 44 , 46 , 47 ), we employed parmbsc1 in this work. Each DNA was immersed into a truncated octahedral box filled by the TIP3P water, ( 48 ) and 24 (class I ) or 28 (classes II, III, C1, C2, H1, H2, H3 ) sodium ( 49 ) cations to maintain electroneutrality.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, molecular dynamics models, fully atomistic [28][29][30][31][32][33][34][35][36][37][38][39][40] or coarse-grained (mesoscopic), [41][42][43][44][45][46] provide different insight into the mechanics of the nucleic acids. The specific choice of the level of granularity of the models depends on the problem at hand.…”
Section: Introductionmentioning
confidence: 99%
“…36 These refinements have become an essential process in order to obtain accurate results in the microsecond timescale. Comparative studies of the common nucleic acid force fields have been performed to evaluate the mesoscale properties of DNA, 37 and to reproduce NMR structures of the Drew-Dickerson dodecamer (DDD) system. 35 Minhas et al found the CHARMM27 model to have the most stable trajectories and best agreement to the experimental data for describing the mesoscale properties of multimicrosecond simulations of long DNA fragments (40 base pairs) in a cubic solvation box of TIP3P water.…”
Section: Introductionmentioning
confidence: 99%
“…While the study revealed both AMBER family models to have good agreement with the experimental data, the CHARMM36 model had unstable trajectories in the microsecond timescale and produced irreversible fluctuations. 37 Whether the choice of force field can affect the pathways and free energy landscape of the conformational transition between the WC and HG base pairing forms is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation